1977
DOI: 10.1083/jcb.73.2.354
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-induced redistribution of lysosomal proteins in rat preputial gland. Evidence from immunologic probes.

Abstract: The influence of estrogen on the subcellular localization and distribution of lysosomal components of preputial gland was investigated in the ovariectomized rat. Antisera of high titer and specificity toward high-density lysosomal lipoproteins of this organ were raised in rabbits. The immunologic effectiveness of the IgG fraction so obtained was confirmed by microcomplement fixation, immunodiffusion, and immunoelectrophoresis. By both direct and indirect immunofluorescence techniques, cryostat sections of prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…RNase activity seen in the E2 treated nuclear fraction, although not significant, was opposite to the E2 effect on all of the other cell fractions. Some investigators (Szego 1972;Szego, Nazareno and Porter 1977) have reported that E2 stimulated an increased lysosomal protein and RNase activity in the nucleus of the ovariectomized rat preputial gland.…”
Section: Discussionmentioning
confidence: 99%
“…RNase activity seen in the E2 treated nuclear fraction, although not significant, was opposite to the E2 effect on all of the other cell fractions. Some investigators (Szego 1972;Szego, Nazareno and Porter 1977) have reported that E2 stimulated an increased lysosomal protein and RNase activity in the nucleus of the ovariectomized rat preputial gland.…”
Section: Discussionmentioning
confidence: 99%